Cleft palate caused by congenital teratoma - Veyssière, Alexis; Streit, Libor; Traoré, Hamady; Bénateau, Hervé (Paediatrics and international child health, 2017)
A cleft palate results from incomplete fusion of the lateral palatine processes, the median nasal septum and the median palatine process. This case report describes a rare case of congenital teratoma originating from the nasal septum that may have interfered with the fusion of the palatal shelves during embryonic development, resulting in a cleft palate. An infant girl was born at 40 weeks of gestation weighing 3020 g with a complete cleft palate associated with a large central nasopharyngeal tumour. Computed tomography (CT) of the head showed a well defined mass of mixed density. The tumour was attached to the nasal septum in direct contact with the cleft palate. A biopsy confirmed the teratoma. Tumour resection was performed at 5 months, soft palate reconstruction at 7 months and hard palate closure at 14 months. There was no sign of local recurrence 1 year later. Most teratomas are benign and the prognosis is usually good. However, recurrence is not rare if germ cell carcinomatous foci are present within the teratoma. For these reasons, we advocate the use of a two-stage procedure in which closure of the cleft palate is postponed until histological examination confirms complete excision of the teratoma.
Keywords: Cleft palate; Cleft Palate; Female; Infant; Teratoma; ženské pohlaví; Tomography, X-Ray Computed; biopsie; lidé; rozštěp patra; nádory nosu; Benign teratoma; teratom; hlava; kojenec; Biopsy; počítačová rentgenová tomografie; Nose Neoplasms; Head; Humans